Трансформація механізму оподаткування доходів населення в умовах пожвавлення міждержавної конкуренції економічних систем - Zhebchuk, Roman; Kindzerskyy, Vitaliy (ТОВ "ДКС Центр", 2020)
У статті проаналізовано важливість вдосконалення державного регулювання оподаткування доходів населення в умовах підвищеного впливу глобальних фінансових шоків на економічний розвиток країн та посилення ролі міждержавної конкуренції в боротьбі за розміщення трудових ресурсів. Зауважено на тому, що основною метою державного регулювання доходів на рівні домогосподарств має бути справедливий перерозподіл доходів, який має сприяти зниженню нерівності, диференціації, а також бути соціально справедливим й економічно обґрунтованим. Визначено ряд недоліків чинного механізму оподаткування доходів населення в Україні та головні завдання податкової політики у сфері соціального розвитку. Ефективність оподаткування, як елемент конкурентних переваг, має досягатись через баланс двох складових: максимізація коригуючого впливу податків від вад ринку та мінімізація впливу податків на вибір платника (щодо сфери отримання та витрачання доходу). Обґрунтовано важливість використання прогресивного оподаткування доходів населення як інструменту досягнення справедливості перерозподілу доходів та неподаткових інструментів для коригування впливу фіскальної політики на доходи населення.
Transformation of the taxation mechanism of population income in terms of intensification of economic systems’ interstate rivalisation
The article analyses the importance of improving state regulation of personal income taxation in the context of increased impact of global financial shocks on economic development and strengthening the role of interstate competition in the struggle for the allocation of labour resources. It is noted that the main goal of state regulation of income at the household level should be a fair redistribution of income, which should help reduce inequality, differentiation, as well as be socially just and economically justified. A number of shortcomings of the current mechanism of personal income taxation in Ukraine (uneven tax burden; lack of differentiated approach to taxation; unstable regulatory framework; multiple taxation and significant tax pressure on the legal sector of the economy; significant costs of taxpayers' resources to comply with tax legislation) main tasks of tax policy in the field of social development (formation of a tax system that stimulates employment and self-employment; establishment of objective and economically justified limits of tax burden on personal income; compliance with the principle of social justice in income taxation of different categories of taxpayers; reduction of inequality and differentiation of the level of redistribution of income). The change in the dynamics of labour market indicators and tax revenues to the consolidated budget of Ukraine for the year spent in quarantine restrictions and noted that an important role in filling the budgets play not only the rules of taxation of various types of income, their administration, the nature of tax benefits in general, but the width of the tax base, the size of tax rates and the number of taxpayers. The effectiveness of taxation, as an element of competitive advantage, should be achieved through a balance of two components: maximizing the corrective effect of taxes on market failures and minimizing the impact of taxes on the payer's choice (in terms of income). The importance of using progressive income taxation as a tool to achieve fair income redistribution and non-tax instruments to adjust the impact of fiscal policy on the quality of life of the population is substantiated.
Keywords: доходи населення; державне регулювання; податкова політика; міждержавна конкуренція